Modeling and Real-Time Simulation of Induction Motor Using RT-LAB - A. Hamed; A. Hazzab (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents the modeling and real-time simulation of an induction motor. The RT- LAB simulation software enables the parallel simulation of power drives and electric circuits on clusters of a PC running QNX or RT- Linux operating systems at sample time below 10 µs. Using standard Simulink models including SimPowerSystems models, RT-LAB build computation and communication tasks are necessary to make parallel simulation of electrical systems. The code generated by the Real-Time Workshop of RT- LAB is linked to the OP5600 digital real-time simulator. A case study example of real-time simulation of an induction motor system is presented.This paper discusses methods to overcome the challenges of real-time simulation of an induction motor system synchronizing with a real-time clock.